INNOVATIVE TECHNOLOGIES FOR INCREASING THE TECHNOLOGICAL SAFETY OF CONVERTER PRODUCTION - Румянцев, В.Р.; Шарапова, Т.А.; Нетяга, В.І. (SWorldJournal, 2023)
The work considers innovative technologies for increasing man-made safety on the example of converter production. In order to find rational means of protecting workers, a hardware and technological diagram of dangerous process zones has been developed. It